2019
DOI: 10.4028/www.scientific.net/kem.801.166
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Boron Concentration on Mechanical Properties of Ni-W-B Composite Coatings

Abstract: Ni-W-B alloy coating containing amorphous boron particle were fabricated by direct current electrodeposition on low carbon steel substrates. The effect of boron concentration in the plating bath on the surface morphology, the overall boron content in the deposited layers and the hardness of the resulting coating layer were investigated. Scanning electron microscopy (SEM) revealed that the surface morphology of the Ni-W-B coating layer was largely modified by the boron particle loading in the electroplating sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The Ni-W coating has an average surface roughness (Ra) of 1.58 ± 0.1 µ m, while the Ni-W/B coatings have Ra values of 1.38 ± 0.05, 1.26 ± 0.07, and 0.93 ± 0.04 µ m, for boron concentrations of 0.5, 1, and 3 g/L in the plating solution, respectively. The incorporation of boron provided a smooth surface of the coatings because the incorporated particles act as nucleation sites and enable grain refinement, resulting in smaller grains [19,29,30], as shown in previous works [4,23,31]. In addition, boron particles retard the crystalline growth of the Ni-W matrix coating, leading to a smoother and more uniform surface [4,29,30].…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The Ni-W coating has an average surface roughness (Ra) of 1.58 ± 0.1 µ m, while the Ni-W/B coatings have Ra values of 1.38 ± 0.05, 1.26 ± 0.07, and 0.93 ± 0.04 µ m, for boron concentrations of 0.5, 1, and 3 g/L in the plating solution, respectively. The incorporation of boron provided a smooth surface of the coatings because the incorporated particles act as nucleation sites and enable grain refinement, resulting in smaller grains [19,29,30], as shown in previous works [4,23,31]. In addition, boron particles retard the crystalline growth of the Ni-W matrix coating, leading to a smoother and more uniform surface [4,29,30].…”
Section: Resultsmentioning
confidence: 52%
“…In our previous work, we reported that the original Ni-W alloy coatings and composite Ni-W coatings modified by adding amorphous boron particles (Ni-W/B) can be successfully deposited on carbon steel using the electrodeposition method [4,23,24]. The hardness and wear resistance of the coatings are significantly improved via the incorporation of an appropriate content of amorphous boron particles because these particles uniformly distribute and provide a smooth surface [4,23]. Furthermore, the incorporated particles in Ni-W coatings can enhance the corrosion resistance [1][2][3][17][18][19].…”
Section: Introductionmentioning
confidence: 99%